IMPROVING THE EARLY LITERACY SKILLS OF 5-6 YEAR OLD CHILDREN THROUGH THE USE OF READING BOX MEDIA AT ALAM PURWAKARTA KINDERGARTEN - Nurfadhilah, Lulu; Syahidin, Samin (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This study aims to improve the early literacy skills of 5-6 year old children through the use of reading boxes at Alam Purwakarta Kindergarten. The method used in this study is a quantitative approach in classroom action research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection. The subjects in this study were 14 children aged 5-6 years (group B). Data collection techniques included observation and documentation, using instruments such as checklists and child development achievement assessments. The results showed that the use of reading boxes as a teaching aid improved the early literacy skills of 5-6 year old children, with an average pre-cycle score of 52.7% in the beginning to develop (MB) category, increasing to 56.30% (MB) in cycle I, and then increasing again in cycle II to 69.78% in the developing as expected (BSH) category. Thus, it is evident that the reading box is effective in improving the early literacy skills of 5-6- year-old children in a fun way and can increase children’s motivation to learn.